Impairment of GABA inhibition in insomnia disorders: Evidence from the peripheral blood system - Xiang, Ting; Liao, Jiwu; Cai, Yixian; Fan, Mei; Li, Congrui; Zhang, Xiaotao; Li, Hongyao; Chen, Yushan; Pan, Jiyang (Frontiers in Psychiatry, 2023)
Aim To explore the change characteristics and related factors of various indexes of GABAergic system in peripheral blood of patients with insomnia disorder. Methods In this study, a total of 30 patients who met the DSM-5 diagnostic criteria for insomnia disorder and 30 normal controls were included. All subjects had a structured clinical interview with the Brief International Neuropsychiatric Disorder Interview, and PSQI was used to evaluate the sleep status of the subjects. Enzyme-linked immunosorbent assay (ELISA) was used to detect serum γ-aminobutyric acid (GABA), and RT-PCR was used to detect GABAA receptor α1 and α2 subunit mRNA. All data were statistically analyzed using SPSS 23.0. Results Compared with the normal control group, the mRNA levels of GABAA receptor α1 and α2 subunits in the insomnia disorder group were significantly lower, but there was no significant difference in the serum GABA levels between the two groups. And in the insomnia disorder group, there was no significant correlation between the GABA levels and the mRNA expression levels of α1 and α2 subunits of GABAA receptors. Although no significant correlation was found between PSQI and serum levels of these two subunit mRNAs, its component factors sleep quality and sleep time were negatively correlated with GABAA receptor α1 subunit mRNA levels, and daytime function was inversely correlated with GABAA receptor α2 subunit mRNA levels. Conclusion The inhibitory function of serum GABA in patients with insomnia may be impaired, and the decreased expression levels of GABAA receptor α1 and α2 subunit mRNA may become a reliable indicator of insomnia disorder.